‚Opfer‘ – Strukturierung eines herausfordernden Lerngegenstands - Peter, Karin (Österreichisches Religionspädagogisches Forum, 2025)
A differentiated structuring of the learning subject is necessary for the further design of competence-oriented learning paths on the diverse topic of ‘Opfer’. By developing a model framework, the diversity of theological concepts on this topic is made visible and workable. For this purpose, models of Opfer are generated from the theological discourse, further developed for the everyday context and expanded to include models that arise from the perspectives of adolescent students. This provides an analytical tool for current emphases on the subject of ‘Opfer’ in theology and everyday life and a basis for didactic decisions.